Strategi Marketing Politik Pasangan Dinda-Dahlan di Kabupaten Bima-NTB - -, Mawardin (Jurnal Transformative, 2018)
This paper explains the importance of political marketing strategy for winning a local election. The role of political marketing strategy has been able to help couples Dinda-Dahlan to get victory in 2015 local elections in Bima regency. In the context of winning strategy that have been used by the Dinda-Dahlan team, consisting of how to formulate marketing mix that includes the political product, promotion, price, and placement. The implementation of the marketing mix are very effective to persuade voters in political contest.